INDIRECT INCITEMENT TO CRIME AND ITS IMPACT ON ESTABLISHING CRIMINAL LIABILITY: AN ANALYTICAL STUDY IN LIGHT OF IRAQI LEGISLATION, JURISPRUDENCE, AND JUDICIARY - Maher Tariq Abbas (International Journal of Business, Law and Political Science, 2026)
Objective: The aim of this research is to review the facets of "Indirect Incitement to Crime" as a developing intellectual criminal phenomenon, and its impact on the criminal liability system in accordance with the Iraqi legislation. This study is based on a simple problem: The legislative gap in suggestive patterns of incitement from the Iraqi Penal Code No. 111 of1969. Such a gap has resulted in paradoxical metaphors in identifying the exercise of constitutional rights (freedom of expression) from criminal behaviors camouflaged under the pretext of glorification or amplification thereof. Method: In order to achieve the purposes of this study, an analytical method was adopted to analyse penal texts as well as a judicial method to extrapolate trends on behalf of Federal Court of Cassation. This study is divided into four distinct sections, the first reviews methodology and prior literature, the second establishes the jurisprudential framework (juristic conceptions of law); the third discusses legal elements (actus reus and mens rea) while the fourth section terminates in punitive impact and mitigation mechanisms. Results: The most significant results of the research were to be seen in the Iraqi Criminal Policy, which began with the so-called "abstracting" indirect assault predicate in terms of special laws and converting it into a stand-alone (crime hazard) crime. Moreover, the results show that the judiciary throws itself on a "contextual standard" in deciding criminal intent. Novelty: And the paper ends by reiterating the need to codify a clear procedural definition of suggestive incitement, as well as design contemporary prophylactic mechanisms adapted to the digital publicity sphere.